Effects of Phellinus linteus extract on immunity improvement: A CONSORT-randomized, double-blinded, placebo-controlled trial - Ku, Yong Ho; Kang, Jae Hui; Lee, Hyun (Medicine (Baltimore), 2022)
Immunity protects the body from external threats and prevents the development of cancer. Biological response modifiers extracted from natural sources are being actively studied, and the immunostimulatory and anticancer effects of various types of fungi have been reported. However, there are no previous clinical studies on the immune-enhancing effect of Phellinus linteus (PL). Lactate dehydrogenase cytotoxicity assay is a prerequisite in order to get approval for using PL as a raw material in functional supplements and medicines in Korea. However, due to the absence of precedent clinical trials, the use of PL in supplements has been hindered. but there is no precedent clinical trial using it. We conducted a randomized, double-blinded, placebo-controlled trial to confirm the efficacy and safety of PL extract for the improvement of immunity using the lactate dehydrogenase cytotoxicity assay.BACKGROUNDImmunity protects the body from external threats and prevents the development of cancer. Biological response modifiers extracted from natural sources are being actively studied, and the immunostimulatory and anticancer effects of various types of fungi have been reported. However, there are no previous clinical studies on the immune-enhancing effect of Phellinus linteus (PL). Lactate dehydrogenase cytotoxicity assay is a prerequisite in order to get approval for using PL as a raw material in functional supplements and medicines in Korea. However, due to the absence of precedent clinical trials, the use of PL in supplements has been hindered. but there is no precedent clinical trial using it. We conducted a randomized, double-blinded, placebo-controlled trial to confirm the efficacy and safety of PL extract for the improvement of immunity using the lactate dehydrogenase cytotoxicity assay.A total of 98 subjects were enrolled and randomly assigned to 2 groups. Subjects in the PL and placebo groups received 1000 mg of PL extract and 1000 mg of dextrin per day, respectively (one capsule, twice every day for 8 weeks). The primary outcome measured was the activity of natural killer cells. Secondary outcomes were the levels of TNF-α, IFN-γ, IL-1β, IL-2, IL-6, IL-12, IgG1, IgG2, and IgM. Safety was evaluated using laboratory tests.METHODSA total of 98 subjects were enrolled and randomly assigned to 2 groups. Subjects in the PL and placebo groups received 1000 mg of PL extract and 1000 mg of dextrin per day, respectively (one capsule, twice every day for 8 weeks). The primary outcome measured was the activity of natural killer cells. Secondary outcomes were the levels of TNF-α, IFN-γ, IL-1β, IL-2, IL-6, IL-12, IgG1, IgG2, and IgM. Safety was evaluated using laboratory tests.NK cell activity was significantly increased in the PL group compared to the placebo group (P < .05). Despite the absence of significant changes in secondary outcomes, there was a tendency for improvement in the PL group. PL extract-related adverse outcomes, particularly in liver and renal function, were not observed.RESULTSNK cell activity was significantly increased in the PL group compared to the placebo group (P < .05). Despite the absence of significant changes in secondary outcomes, there was a tendency for improvement in the PL group. PL extract-related adverse outcomes, particularly in liver and renal function, were not observed.PL extract may improve immunity and is safe to be consumed orally.CONCLUSIONPL extract may improve immunity and is safe to be consumed orally.